In-Depth Investigation of Antifungal Activity of Compounds of Series of Silver Salts of Pyrazol-3-Carboxamids - V. V. Novikova; V. L. Gein (Антибиотики и Химиотерапия, 2020)
The aim of the study was to investigate the antifungal activity of 4 new promising compounds of pyrazole-3-carboxamides containing silver ion in relation to clinical isolates of Candida spp. using the micromethod of two-fold serial dilution in liquid medium. The article presents the results of an in-depth study of these compounds with respect to the clinical strains of Candida albicans, a typical pathogen causing vulvovaginal candidiasis, as well as to less common non-albicans Candida spp. that are resistant to the most commonly used antimycotics. The compound showing high antifungal activity (MIC50 0.15 mcg/ml, MIC90 6.25 mcg/ml), which is recommended for further preclinical studies, has been identified.